Mushroom growing - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Edible mushrooms can be easily produced in developing countries without sophisticated techniques. In fact, mushrooms grow well on a variety of substrates made of straw or vegetable residues. Furthermore, growing techniques are both simple and...